The Soft Power of Buddhism: Fostering Social Harmony and Cultural Identity in Thai Society - Srichan, Phramaha Danai; Phra Thongjaroen Khotdinkhao; Phramaha Sarayut Nonthapa; Sankaew, Phra Phra Dhammanan (The Journal of International Buddhist Studies College, 2024)
This article investigates the profound influence of Buddhism as a soft power for fostering social harmony and cultural identity in Thailand. Through historical analyses, sociological perspectives, and contemporary case studies, the study elucidates how Buddhism permeates Thai society, impacting governance, familial relationships, and communal rituals. The exploration of Buddhist teachings, ethical values, and institutional frameworks underscores the pivotal role of the Sangha (monastic community) in promoting solidarity, resilience, and moral integrity among Thai citizens. Additionally, the report examines the dynamic interplay between Buddhism and socio-political dynamics, addressing the challenges and opportunities for preserving Buddhist traditions amidst rapid social change and globalization. By illuminating the connections between religion, culture, and social cohesion, this study provides insights into the enduring significance of Buddhism as a unifying force in Thai society.